Pengembangan Pariwisata Halal pada Objek Wisata Linggo Asri Kabupaten Pekalongan: Social Media Approach - Abidiyanto, Mohamad Sahrul; Adinugraha, Hendri Hermawan (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2023)
This research examines advertising or promotion to develop Linggo Asri tourist attraction through social media with the aim of describing in depth the halal tourism development strategy through social media, a study at Linggo Asri tourist attraction, Pekalongan Regency. This research method uses qualitative research and field research. The results of this study indicate that the Linggo Asri Tourism Object in Pekalongan Regency is still very potential to be developed further, if you pay attention to the results of development strategies that exist in tourist attractions, managers can take advantage of this potential to make tourist attractions grow. Not only that, by knowing these strategies, the manager will be able to examine and analyze so that he can make the best decisions in managing the Linggo Asri tourist attraction in the future. Social media plays an important role in the development of Linggo Asri Tourism Objects in Pekalongan Regency. Because indirectly with the use of social media, several aspects related to the development of tourist attractions can be fulfilled and well exposed. Not only that, with the halal tourism standardization that has been explained, Linggo Asri tourist attraction can be categorized as halal tourism which refers to nature tourism, educational tourism, and family tourism. Although there are some things that must be improved again to get a perfect score in the standardization of sharia tourism.